Price changes of reinforced concrete works in the Republic of Croatia: case study of a single-family house project (Proceedings of Faculty of Civil Engineering, 2025)
The topic of this paper is related to major changes and price increases in the construction sector, which have seriously disrupted the implementation of construction projects in the period from 2019 to 2024. The paper analyses the price trends of reinforced concrete works for the specified period using a real example of the construction of a family house in the Republic of Croatia. This paper aims to investigate how market movements impact the prices of selected construction works, as well as to identify the key elements that contribute most to changes in the total price. The project documentation of the selected project served as the basis for calculating prices by year, and the price itself was determined using the standard additional calculation method, applying a calculation factor. According to the results obtained, the total price of reinforced concrete works increased by approximately 93 % within the observed period. The largest share of the total price of works is accounted for by material costs, which amount to as much as 84 %. The causes of price changes include various geopolitical, health and natural disasters, such as the coronavirus pandemic, earthquakes, war in Europe and other consequential events. To mitigate the effects of market instability, more flexible contracting of works, along with improved planning and management of construction projects, is recommended.
Keywords: reinforced concrete works; market instability; family house; price changes